Phytoactinopolyspora limicola sp. nov., an alkaliphilic actinomycete isolated from a soda alkali-saline soil - Wei, Wei; Wang, Kaili; Hu, Xinyu; Yang, Sai; Zeng, Chunlin; Hou, Zhaozhi; Liu, Shenkui; Cui, Henglin; Zhu, Lin (Archives of microbiology, 2021)
An alkaliphilic actinomycete, designated HAJB-30 T , was isolated from a soda alkali-saline soil in Heilongjiang, Northeast China. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain HAJB-30 T was most closely related to type strains of the genus Phytoactinopolyspora with sequence similarities ranging between 93.5 and 98.9%. Strain HAJB-30 T grew at pH 8.0–11.0 (optimum pH 9.5–10.0) and in the presence of 0–7.0% NaCl (optimum 1.0–3.0%). Whole-cell hydrolysates of the isolate contained LL-diaminopimelic acid as the diagnostic diamino acid and mannose and rhamnose as diagnostic sugars. The major fatty acids identified were iso-C 14:0 , iso-C 15:0 , anteiso-C 15:0 , iso-C 16:0 and anteiso-C 17:0 , while the menaquinone was MK-9(H4). The genome (6,589,901 bp), composed of 50 contigs, had a G + C content of 66.8%. Out of the 6074 predicted genes, 6020 were protein-coding genes, and 54 were ncRNAs. Digital DNA–DNA hybridization (dDDH) estimation and average nucleotide identity (ANI) of strain HAJB-30 T against genomes of the type strains of related species in the same family ranged between 19.7 and 22.0% and between 71.5 and 76.8%, respectively. From these results, it was concluded that strain HAJB-30 T possesses sufficient characteristics differentiated from all recognized Phytoactinopolyspora species, it is considered to be a novel species for which the name Phytoactinopolyspora limicola sp. nov. is proposed. The type strain is HAJB-30 T (= CGMCC 4.7591 T , = JCM 33694 T ).